Echolocation repetition rate as a proxy to monitor population structure and dynamics of sperm whales. Issue 6 (8th June 2022) - Solsona‐Berga, Alba; Posdaljian, Natalie; Hildebrand, John A.; Baumann‐Pickering, Simone
Abstract: Characterizing population structure and dynamics is critical for the conservation of endangered species. Monitoring sperm whales Physeter macrocephalus is especially difficult because it requires monitoring different latitudes to capture the dynamics of most populations. Since their remarkable sexual dimorphism in body size is reflected in their sounds, passive acoustic monitoring presents an opportunity to capture contiguous patterns in time, space, and over large scales. We show that the echolocation repetition rate (measured as inter‐click interval, ICI) as a proxy for body length is a suitable approach for large‐scale acoustic monitoring. Body length has previously been estimated from the time interval between pulses (IPI) within sperm whale echolocation clicks. These estimates can only be achieved when whales are oriented toward the recorder or directly facing away, resulting in sparse data. A representative subsample of data demonstrated that ICI and IPI are linearly correlated, allowing conversion of ICI distributions into likely body length categories. This approach was applied to three monitoring sites in the Gulf of Mexico (2010–2017), where sperm whale population structure and male movements were poorly understood. We identified three classes: large animals between 12–15 m (ICI between 0.72 and 1 sec), presumed to correspond to adult males, and small animals below 12 m (ICI between 0.44 and 0.64 sec) likely pertaining to social groups (mixed groups with adult females and their offspring), and the third class with mid‐sized animals (ICI between 0.64 and 0.83 sec) believed to contain adult females or sub‐adult males. Our results revealed spatial and seasonal variability of the population structure including possible male presence throughout the year and migratory patterns of the population. This approach provides a means to efficiently characterize the putative population structure of sperm whales to understand the population's geographical dynamics and population status, which is relevant under rapidly changing habitat conditions. Abstract : Passive acoustic monitoring is an essential method for studying the ecology of endangered sperm whales. We present a novel approach based on their sexual body size dimorphism to monitor population structure and dynamics by using the time interval between echolocation clicks (ICI) as a proxy for body length. Our results suggest that ICI can be used as a proxy for sperm whale body length, with increasing ICI scaling with body size. This approach offers a relatively quick method to characterize acoustic encounters into body size categories. This method applied to seven years of acoustic data revealed migratory patterns and the presence of adult males in the Gulf of Mexico. This constitutes as an important knowledge contribution to the poorly understood subpopulation of this region where male movements and timing of breeding are largely unknown. Applying this approach more broadly may help improve our understanding of this species' global geographical dynamics and population status.